THE INFLUENCE OF GREEN PRODUCT, GREEN BRAND IMAGE, AND BRAND AMBASSADOR ON PURCHASE INTENTION FOR MIE LEMONILO X NCT DREAM - Sauki, Moch Syahrir; Wardani, Nuruni Ika Kusuma; Sholihah, Dewi Deniaty (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
K-pop is a popular trend with a massive fan base. Enthusiasts often exhibit obsessive, consumptive, hysterical, and addictive behaviors toward K-pop-related items. At the Food and Hospitality Indonesia (FHI) 2023 event, Lee Seung Hoon reported remarkable growth in the export of Korean food and beverage products to Indonesia, including a 25.8% increase in instant noodle exports. This research aims to examine the influence of Green Product, Green Brand Image, and Brand Ambassador variables on the Purchase Intention of Lemonilo x NCT Dream products.The study employs a quantitative research method, with a sample size of 80 respondents determined using the Likert formula. The sampling technique applied is Purposive Sampling, and data analysis was conducted using the Partial Least Square (PLS) program. The results reveal that green product, green brand image, and brand ambassador variables significantly influence consumer purchase intention for Lemonilo x NCT Dream products.